2012
DOI: 10.3382/ps.2011-01951
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of hen production type, age, and temperature on laying pattern and egg quality

Abstract: The effect of production type (layer vs. broiler breeder), age (onset and end of laying cycle), and temperature (20 and 28°C) on various aspects of the egg production process and quality was evaluated. Highly significant differences were detected between laying hens and broiler breeders (P ≤ 0.001) in all production parameters. Similarly, age significantly affected rate of lay (P ≤ 0.001; 75.4% for young vs. 62.6% for old), mean sequence length (P ≤ 0.001; 7.7 d for young vs. 2.6 d for old), and time of ovipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 29 publications
4
36
0
3
Order By: Relevance
“…Numerous previous studies suggested that egg weight showed a curvilinear relationship with the increase of hen age (Di Masso et al, 1998;Suk and Park, 2001;Nangsuay et al, 2011;Tumova and Gous, 2012), and provided critical insights into controlling the increase rate of egg weight (Minvielle et al, 1994). However, these authors only evaluated the tendency and increment of egg weight between different weeks of age, lacking full evaluation of their genetic basis.…”
Section: Introductionmentioning
confidence: 94%
“…Numerous previous studies suggested that egg weight showed a curvilinear relationship with the increase of hen age (Di Masso et al, 1998;Suk and Park, 2001;Nangsuay et al, 2011;Tumova and Gous, 2012), and provided critical insights into controlling the increase rate of egg weight (Minvielle et al, 1994). However, these authors only evaluated the tendency and increment of egg weight between different weeks of age, lacking full evaluation of their genetic basis.…”
Section: Introductionmentioning
confidence: 94%
“…Tumova et al [33] obtained 6.91 -7.81g at 28 -60 weeks of age in New Black breed; and 6.50 -6.91g for litter raised Hisex Brown at 60 weeks. However, Ewa et al [28] …”
Section: Phenotypic Least Square Means and Standard Error Of Egg Qualmentioning
confidence: 99%
“…Egg weight was increased progressively and significantly (P < 0.001) with increasing age of birds except 51 to 60-week age group. Tumova and Goust [24] studied the interaction of hen production type, and temperature on laying pattern and egg quality. The result revealed that a significant interaction between type and age (P < 0.015) was evident in egg weight, but egg component proportions were dependent only on hen type.…”
Section: Age Of Laying Henmentioning
confidence: 99%
“…Several studies observed such a decline in most of the traits that were evaluated in layers, with the exception of egg weight, which increased with age [23][24][25]27]. Egg weight is an expression of the overall egg size, and optimum egg size, and optimum egg size varies according to the market in different countries [7].…”
Section: Age Of Laying Henmentioning
confidence: 99%
See 1 more Smart Citation